Organizational Communication and Change's effects on Employee Perceptions: - (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Adaptation and progress within an organization are emphasized in this study. Each successfulbusiness knows that it must constantly evolve and change in order to be competitive in its market. Asbusinesses start to lag behind, they need to make changes to their strategy in order to catch up.Businesses that are willing to adapt to new circumstances have a better chance of succeeding in theirmissions. The purpose of the research was to identify the characteristics of organizational communicationand evaluate its relative efficacy. Research on the effects of organizational change on performance on thejob provide the basis for the findings. For efficient internal communication and employee productivity inany business, it is crucial to have a firm grasp of the many facets of organizational communication.Successful communication is first recognized, and then the connection between organizationalcommunication and employee output is determined.